Electrode/Electrolyte Optimization-Induced Double-Layered Architecture for High-Performance Aqueous Zinc-(Dual) Halogen Batteries - Zhou, Chengwang; Ding, Zhezheng; Ying, Shengzhe; Jiang, Hao; Wang, Yan; Fang, Timing; Zhang, You; Sun, Bing; Tang, Xiao; Liu, Xiaomin (Nano-Micro Letters, 2024)
Aqueous zinc-halogen batteries are promising candidates for large-scale energy storage due to their abundant resources, intrinsic safety, and high theoretical capacity. Nevertheless, the uncontrollable zinc dendrite growth and spontaneous shuttle effect of active species have prohibited their practical implementation. Herein, a double-layered protective film based on zinc-ethylenediamine tetramethylene phosphonic acid (ZEA) artificial film and ZnF2-rich solid electrolyte interphase (SEI) layer has been successfully fabricated on the zinc metal anode via electrode/electrolyte synergistic optimization. The ZEA-based artificial film shows strong affinity for the ZnF2-rich SEI layer, therefore effectively suppressing the SEI breakage and facilitating the construction of double-layered protective film on the zinc metal anode. Such double-layered architecture not only modulates Zn2+ flux and suppresses the zinc dendrite growth, but also blocks the direct contact between the metal anode and electrolyte, thus mitigating the corrosion from the active species. When employing optimized metal anodes and electrolytes, the as-developed zinc-(dual) halogen batteries present high areal capacity and satisfactory cycling stability. This work provides a new avenue for developing aqueous zinc-(dual) halogen batteries. Highlights: 1 A double-layered protective film based on zinc-based coordination compound and ZnF2-rich solid electrolyte interphase layer has been successfully fabricated on the zinc metal anode via electrode/electrolyte synergistic optimization. 2 The double-layered architecture can effectively modulate Zn2+ flux and suppress the zinc dendrite growth, thus facilitating the uniform zinc deposition. 3 The as-developed zinc-(dual) halogen batteries based on double-layered protective film can present high areal capacity and satisfactory cycling stability.